Maternal low-protein diet reduces skeletal muscle protein synthesis and mass via Akt-mTOR pathway in adult rats - de Vasconcelos, Diogo Antonio Alves; Nachbar, Renato Tadeu; Pinheiro, Carlos Hermano; do Amaral, Cátia Lira; Crisma, Amanda Rabello; Vitzel, Kaio Fernando; Abreu, Phablo; Alonso-Vale, Maria Isabel; Lopes, Andressa Bolsoni; Bento-Santos, Adriano; Falcão-Tebas, Filippe; de Santana, David Filipe; et al. (Frontiers in Nutrition, 2022)
Several studies have demonstrated that maternal low-protein diet induces long-term metabolic disorders, but the involved mechanisms are unclear. This study investigated the molecular effects of low-protein diet during pregnancy and lactation on glucose and protein metabolism in soleus muscle isolated from adult male rats. Female rats were fed either a normal protein diet or low-protein diet during gestation and lactation. After weaning, all pups were fed a normal protein diet until the 210th day postpartum. In the 7th month of life, mass, contractile function, protein and glucose metabolism, and the Akt-mTOR pathway were measured in the soleus muscles of male pups. Dry weight and contractile function of soleus muscle in the low-protein diet group rats were found to be lower compared to the control group. Lipid synthesis was evaluated by measuring palmitate incorporation in white adipose tissue. Palmitate incorporation was higher in the white adipose tissue of the low-protein diet group. When incubated soleus muscles were stimulated with insulin, protein synthesis, total amino acid incorporation and free amino acid content, glucose incorporation and uptake and glycogen synthesis were found to be reduced in low-protein diet group rats. Fasting glycemia was higher in the low-protein diet group. These metabolic changes were associated with a decrease in Akt and GSK-3β signaling responses to insulin and a reduction in RPS6 in the absence of the hormone. There was also notably lower expression of Akt in the isolated soleus muscle of low-protein diet group rats. This study is the first to demonstrate how maternal diet restriction can reduce skeletal muscle protein and mass by downregulating the Akt-mTOR pathway in adulthood.